Two cases of combined immunodeficiency with ITPR3 mutations presenting with life-threatening severe EBV-associated hemophagocytic lymphohistiocytosis - Yu, Lang; Li, Yulin; Zhang, Liwen; Li, Wenhui; Sun, Ming; An, Yunfei; Xiong, Hao; Jin, Peina; Zhao, Xiaodong (Frontiers in Immunology, 2025)
IntroductionITPR3 encodes a subunit of the inositol 1,4,5-trisphosphate receptor (IP3R), which forms a Ca2+ channel on the endoplasmic reticulum (ER) membrane responsible for ER Ca2+ release. Recently, both autosomal dominant and recessive ITPR3 mutations have been reported in association with combined immunodeficiency (CID), accompanied by multisystem manifestations including neurological involvement. MethodsWe retrospectively analyzed the clinical characteristics of two patients with ITPR3 deficiency accompanied by hemophagocytic lymphohistiocytosis (HLH) at our center. Through a literature review, we further compared their clinical manifestations with those of combined immunodeficiency (CID) patients who presented with HLH.Results and DiscussionsOur two CID patients with multisystem disorders harboring germline heterozygous ITPR3 mutations (c.7570C>G, p.Arg2524Gly and c.7570C>T, p.Arg2524Cys). Both patients developed severe Epstein-Barr virus (EBV)-associated HLH, and one patient succumbed to disease-related complications. Our study demonstrates that ITPR3-associated CID confers a susceptibility to EBV-driven pathologies, particularly HLH, which warrants heightened clinical vigilance. Therefore, early hematopoietic stem cell transplantation (HSCT) should be considered to improve survival outcomes in these patients.